Adopting accessory dwelling units: a case study of Manhattan, Kansas - Frohberg, Lesley Danielle (Kansas State University, 2019)
In the United States, millions of people are considered cost-burdened when paying for housing, meaning more than 30% of their income is used for housing cost (Thrush, 2018). Affordable housing has continued to be an issue in rapidly growing communities that lack a diverse and sufficient housing stock. To alleviate housing issues, many municipalities are turning to alternative methods to provide more housing opportunities, such as accessory dwelling units. While a solution for our nation’s housing issues go far beyond accessory dwelling units, they do bring a diversified and affordable housing option to communities without extensive government intervention.   As secondary units within single-family residential neighborhoods, accessory dwelling units provide many benefits to property owners, renters, and the community. The City of Manhattan, Kansas, took interest in permitting this housing type within their community but due to lack of support, it ultimately failed. To gain a more in depth understanding of the most effective accessory dwelling unit policy adoption process, I will examine three other cities that have successfully implementing ADUs into their communities; Boulder, Colorado; College Station, Texas; and Lawrence, Kansas. To gather information from the cities I will use case study research and interviews with City Staff. I will then examine the adoption processes the identified cities executed to educate their residents on the proposed policy in effort to gain support from the public and elected officials. A conclusion will be formed by synthesizing the results of a cross-case comparison using document analysis and grounded theory inspired analysis. The aim of this research is to provide the City of Manhattan, Kansas’s Community Development Department with recommendations on an effective accessory dwelling unit policy and public education and engagement process.
Keywords: Accessory dwelling unit; Manhattan, Kansas; Housing; Land use regulations